UMA INVESTIGAÇÃO SOBRE O PENSAMENTO COMPUTACIONAL COM O USO DA PLATAFORMA PROGRAMAÊ! - GERMANO, ANA PAULA (2022)
Computational Thinking (CT) can be understood as an approach to problem solving, systems design and understanding human behavior that uses fundamental concepts of computer sciense, a fundamental skill for everyone. Considering the need to develop skills and abilities that stimulate CT, education professionals should provide students with appropriate and motivating practices for this purpose. In this context, this research aim is investigate the development of the PC through the Programaê! platform, which uses block based programming as a tool for this purpose. For this, a roadmap of activities for the Programaê! platform was prepared, aiming to stimulate CT in students of Secondary Technical Education. The teaching experience involved students in the 1st year of the Technical Course in Informatics at Colégio Estadual Francisco Carneiro Martins, in Guarapuava-PR. Data collected during the teaching experience were analyzed following the content analysis methodology. The analysis consisted of relating the practices adopted during the development of the selected activities to the four CT dimensions (also called pillars): abstraction, decomposition, pattern recognition and algorithms. The results showed that the students developed CT skills, according to the dimensions, which is evidenced by the adequate use of programming elements (events, loops, selection structures and functions) in the proposed activities. Considering CT as a transverse theme, the didactic product resulting from this research constitutes a roadmap of activities to support teachers from different disciplines, who seek to encourage the development of CT skills.